The Blog is Dead, Long Live the Blog! Analysis of Blogs on Spanish Radio Stations - María Olivera Zaldua; Juan Miguel Sánchez Vigil; Juan Carlos Marcos Recio (Index Comunicación, 2015)
Blogs linked to the various media channels have changed considerably over the last five years as a direct result of the growth of the social networks, and they now occupy a secondary position, at least in terms of visibility. In theory one of the media where you would expect them to be least used is the radio, even if there are no specific studies to the effect. Beginning from this hypothesis, the aim of this work is to analyze the blogs on the major Spanish radio stations with a nationwide audience, both public and private, to quantify and categorize the content, check links to specific programs and gain an understanding of their current activity. With the results obtained it was concluded that the creation of blogs has been maintained in the last three on this list since 2010, with a considerable increase on La COPE; that subject matter is varied, with particular focus on Cultural topics and Sport and that the longest running active blog is ‘El Larguero’ (the crossbar) on Cadena SER.